Policy-based service provisioning architecture for hybrid photonic networks - Fawaz, Wissam (2017)
Optical networks are becoming an inevitable technology in the next generation Internet. Optical WDM networks require a control network for automatic and rapid configuration. A control plane is under standardization by the Internet Engineering Task Force (IETF) under the name generalized multiprotocol label switching (GMPLS). However, this control plane is unaware of the specifications of the services to be enforced. This work presents a policy-based management architecture adapted to an emerging kind of optical networks called hybrid photonic networks. Contributing to network flexibility, we present extensions to the management plane of these transparent wavelength and switching capable networks that provide the means to leverage their inherent capabilities. The proposed management architecture would provide optical network operators with the possibility to provision optical services, defined through high level service contracts, in an efficient and dynamic way.